Role of GeneXpert in endometrial biopsy for diagnosis of genital tuberculosis in women presenting with infertility - Naaz, Aafreen; Sarbhai, Vikram; Sarbhai, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The diagnosis of female genital TB is challenging due to low sensitivity of conventional diagnostic modalities. The new GeneXpert Test on endometrial biopsy is studied for its role in diagnosis of female genital TB. Methods: This is an observational cross-sectional study on 50 infertile women. Premenstrual endometrial biopsy was performed and sent for AFB Smear, M. TB (LJ) medium culture, CB-NAAT by GeneXpert, and histopathology. The results were compared for diagnosis of FGTB. Results: Endometrial Biopsy (EB) could confirm diagnosis of genital TB in 4 cases (8%) out of 50 infertile women. Amongst these 4 cases, GeneXpert was positive in two, AFB were detected on smear in three while one showed both AFB on smear and positive GeneXpert. GeneXpert adds additional value but surely cannot replace any of the other gold standard investigations. Conclusions: GeneXpert is a rapid diagnostic method which is accurate, feasible and affordable. It is useful adjunct to the existing armamentarium in diagnosis of female genital tuberculosis.